The Application of Technology Acceptance Model for User Perception of Odoo Information System: The Application of Technology Acceptance Model for User Perception of Odoo Information System - Haryani Haryani; Rahmat Hidayat; Titik Misriati; Instianti Elyana (Jurnal Mantik, 2020)
The strategic role of information systems is to help management in providing information that can support decision making. Companies need to think about how information systems that are already owned and will be developed to achieve success. The purpose of this study is to predict user acceptance of Odoo information system at PT. Cardig Anugrah Sarana Catering (CASC) using the Technology Acceptance Model (TAM) based on the effect of perceived ease of use, perceived usefulness and the addition of perceived user attitudes (attitude toward using) to Odoo information systems. The results of this study that the use of Odoo information system can be well received by users of information systems in PT. Cardig Anugrah Sarana Catering.